Synthesis and Characterisation of Non-Fullerene Electron Acceptors for Organic Photovoltaics - Holliday, Sarah (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book reports on the design, synthesis and characterization of new small molecule electron acceptors for polymer solar cells. Starting with a detailed introduction to the science behind polymer solar cells, the author then goes on to review the challenges and advances made in developing non-fullerene acceptors so far. In the main body of the book, the author describes the design principles and synthetic strategy for a new family of acceptors, including detailed synthetic procedures and molecular modeling data used to predict physical properties. An indepth characterization of the photovoltaic performance, with transient absorption spectroscopy (TAS), photo-induced charge extraction, and grazing incidence X-ray diffraction (GIXRD) is also included, and the author uses this data to relate material properties and device performance. This book provides a useful overview for researchers beginning a project in this or related areas.